Effect of Non-Performing Loans (NPL), Operational Efficiency Ratio (BOPO) on Return on Assets at Conventional Banks - Yona Kristianto Budiman; Stephanus Stephanus; Astri Yunisa (Jurnal Ad'ministrare, 2022)
This study aims to find the effect of non-performing loans (NPL), operational efficiency ratio (BOPO) on return on assets (ROA) at banks in Indonesia for the period 2020. The banking sector is very important because it is conventionally expected to support the government to increase economic growth, but during the pandemic which began in the 2nd quarter of 2020, all sectors have decreased in performance, one of which was banking, due to the inability of customers to pay their credit bills. The object of this research is the financial statements of conventional banks in 2020 with the research method used is explanatory. The population in this study is conventional bank sector in 2020, with a population of 95 banks, and the data analysis used is multiple linear regression . The results show that Non-Performing Loans (NPL) do not significantly affect Return on Assets (ROA) whereas Operational Efficiency Ratio (BOPO) affects Return on Assets (ROA).